Hybrid PWM DC/DC converter for EV on-board charger with single transformer. Issue 2 (3rd April 2018) - Choi, Jin-Yong; Choi, Seung-Won; Lee, Jun-Young
Abstract: This paper suggests a hybrid PWM DC/DC converter comprised of the Full-Bridge (FB) converter and the PWM resonant converter for on-board chargers. It has hybrid characteristics having output characteristics of the FB converter and switching characteristics of the PWM resonant converter. They are coupled in a single transformer so that the power distribution problem which causes increase of the transformer size can be solved. Because the transformer leakage inductance is used as a resonant parameter and the output inductor current ripple is very small, a dissipative snubber circuitry and output current filter can be removed. Zero-voltage-zero-current switching(ZV-ZCS) operation of bottom switches and ZVS operation of top switches can be accomplished by a proper design of the resonant parameter. The feasibility of the proposed charger is verified with a 6.6 kW prototype.